Electrochemical Detection of Dopamine using a Phenyl Carboxylic Acid‐Functionalized Electrode Made by Electrochemical Reduction of a Diazonium Salt. Issue 12 (7th December 2022) - Anjum, Saima; Lou, Baohua; Tahir, Amiza; Aziz‐ur‐Rehman,; Rehan H. Shah Gilani, M.; Xu, Guobao
Abstract: A glassy carbon electrode (GCE) has been modified by an in situ electrochemical reduction of an aryldiazonium salt generated from the reaction of 4‐aminobenzoic acid and sodium nitrite in acidic ethanolic solution. The as‐prepared phenyl carboxylic acid‐modified glassy carbon electrode has been, for the first time, used for the electrochemical determination of dopamine. Under optimal experimental parameters, outstanding electrocatalytic activity, high sensitivity at a LOD of 5.6×10 −9 m, and broad linearity of 0.1 to 1000 μm were obtained. The crafted electrochemical platform demonstrated excellent stability, specificity, and anti‐interference capability towards the sensing of dopamine. Abstract : A robust phenyl carboxylic acid‐modified electrode has been prepared by electrochemical reduction of a diazonium salt. The surface of the modified electrode is negatively charged, enabling not only sensitive detection of dopamine but also excellent selectivity in the presence of ascorbic acid.